An Acoustic Analysis Of Plosive Sounds Produced By Indonesian ELF University Students - Khopifah Nurmutiarohmah Aini Mutia; Susie Chrismalia Garnida (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This research explore the dimensions of acoustic phonetics in linguistic context with a focus on the analysis of sound sounds in a particular language. The purpose of this research to investigate differences in the pronunciations of consonant sounds between native and non-native speakers of the language. Use a phonetic-acoustic approach by analyzing voice data using the Praat application. The data used in this study consisted of recorded from native speakers and non-native speakers of that language. This research uses qualitative method, from use the recording and use Praat to collect the data. Pronunciation by 11 students from East Javanese.